Vortex singing in tip vortex cavitation under the effect of water quality. (November 2015) - Peng, Xiaoxing; Xu, Lianghao; Song, Mingtai; Cao, Yantao
Abstract: The phenomenon of vortex singing in tip vortex cavitation is studied experimentally in this paper. It is revealed that the vortex singing can be observed during the vortex cavity transfer from one phase to another in the same incoming flow condition. The state of vortex singing can only exist in a short duration from several seconds to several minutes. The sound of the vortex singing for different water qualities, including air content and nuclei populations of water are measured by a hydrophone. It is found that the tones of vortex singings are very different under different flow conditions and water qualities.